Computer‐aided analysis and design procedure for rotating induction machine magnetic circuits and windings. Issue 6 (9th May 2018) - Caruso, Massimo; Di Tommaso, Antonino O.; Miceli, Rosario; Rizzo, Renato
Abstract : The aim of this study is to present a new, accurate, and user‐friendly software procedure for the analysis and rapid design of rotating induction machine windings, considering both the electric and the magnetic specifications of the machine itself. This procedure is a valid aid for quick first stage design without the necessity of using finite element method (FEM)‐based design procedures. FEM can be used in a second design phase in order to refine the first stage results. The design procedure is hereafter outlined and some examples show its capability.